2019
DOI: 10.1115/1.4045334
|View full text |Cite
|
Sign up to set email alerts
|

A Gaussian Process Model-Guided Surface Polishing Process in Additive Manufacturing

Abstract: Polishing of additively manufactured products is a multi-stage process, and a different combination of polishing pad and process parameters is employed at each stage. Pad change decisions and endpoint determination currently rely on practitioners’ experience and subjective visual inspection of surface quality. An automated and objective decision process is more desired for delivering consistency and reducing variability. Toward that objective, a model-guided decision-making scheme is developed in this article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…So it is certainly applicable to detecting surface quality changes on a flat surface as well. We take the data from the flat surface polishing experiment published in Jin et al (2020) and test the proposed method on it. For the details on that polishing experiment, please refer to Jin et al (2020).…”
Section: Methods Regression Test On a Flat Surfacementioning
confidence: 99%
See 4 more Smart Citations
“…So it is certainly applicable to detecting surface quality changes on a flat surface as well. We take the data from the flat surface polishing experiment published in Jin et al (2020) and test the proposed method on it. For the details on that polishing experiment, please refer to Jin et al (2020).…”
Section: Methods Regression Test On a Flat Surfacementioning
confidence: 99%
“…Recent works (Wang et al, 2014;Liu et al, 2017;Bukkapatnam et al, 2018;Jin et al, 2020) showed people's awareness of a number of critical limitations of using average metric such as Sa or median Sa for the finishing process of precise manufacturing. Jin et al (2020) provided specific examples where a set of similar media Sa values correspond to surfaces with rather different roughness features. Jin et al (2020) further proposed a new decision making criterion for polishing by modeling the surface roughness at each stage through a Gaussian process (GP).…”
Section: Decision Making In Polishing Processesmentioning
confidence: 99%
See 3 more Smart Citations